PELATIHAN PENGGUNAAN COCA DALAM PENELITIAN LINGUISTIK BAGI MAHASISWA JEPANG SEBUAH PROGRAM PENGABDIAN PADA MASYARAKAT KOLABORATIF INTERNASIONAL - Rizdika Mardiana; Dwi Astuti; Muhammad Ali Hamdi; Bambang Nur Alamsyah Lubis; Muchlas Suseno (LPPM Institut Pendidikan Nusantara Global, 2025)
In the era of globalization and rapid digital technological advancement, approaches to linguistic research have undergone significant transformation. One increasingly popular approach is corpus linguistics, which utilizes digital language data to analyze real and contextual language use. To introduce this method to international students, an International Community Service (P2M) program was held in the form of a training session themed